Training on Village Regulation Making in North Sumatra Villages - Ritonga, Fajar; Suriadi, Agus; Siregar, Hendra Dermawan (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This training on making village regulations aims to help village officials provide Village Minimum Service Standards in implementing the policy of the Minister of Home Affairs Regulation Number 2 of 2017 which consists of 6 minimum standards of facilities and infrastructure and 22 minimum standards of other public services. The implementation was carried out in 4 days starting with a focus group discussion, and continued with a workshop on making village regulations, the location of the service was carried out at the Paya Pasir Village Hall and Cempedak Lobang Village, Serdang Bedagai Regency. After the Focus Group Discussion, it was known that information from the village apparatus that the implementation of the Village Minimum Service Standards had not been fulfilled, this was due to the lack of understanding and insight of the village apparatus. The workshop was conducted as a form of socialization and understanding of the Minister of Home Affairs Regulation Number 2 of 2017 and training in making village regulations on technology-based village minimum service standards using website applications to make it easier for people to get public services from home using only smart phones that can be accessed by the village community and avoid brokers and illegal levies from irresponsible individuals or parties